FRI0205 CLINICAL FEATURES OF MONONEURITIS MULTIPLEX ASSOCIATED WITH ANCA-ASSOCIATED VASCULITIS. (13th June 2020) - Hama, S.; Hayashi, Y.; Izumi, K.; Higashida-Konishi, M.; Ushikubo, M.; Akiya, K.; Okano, Y.; Oshima, H.
Abstract : Background: ANCA-associated vasculitis sometimes presents mononeuritis multiplex which worsens the prognosis and activity of daily living in patients. Objectives: This study aimed to determine the clinical feature of mononeuritis multiplex associated with AAV. Methods: Consecutive patients with AAV who visited Tokyo Medical Center between April 2006 and December 2019 were included in this study. We examined the following clinical features: prevalence of neuropathy, age of onset, sex, the worst blood test values before the initial therapy (white blood cell count (WBC), eosinophil count (Eo), MPO-ANCA, PR3-ANCA, and C-reactive protein(CRP) levels), manual muscle testing (MMT)score of 20 muscles (Max 100 points), and time (days) from the initial symptoms to the initial induction therapies. Results: A total of 89 patients with AAV were identified. Among them, 19 patients had eosinophilic granulomatosis with polyangiitis (EGPA) (8 males and 11 females, mean age 63.3 ± 2.7), 9 patients had granulomatosis with polyangiitis (GPA) (0 males, 9 females, mean age 75.6 ± 3.9), and 61 patients had microscopic polyangiitis (MPA) (17 males, 44 females, mean age 78.2 ± 1.5). Of the 89 AAV patients, 26 had sensory neuropathy (15/19 EGPA (78.9%), 11/61 MPA (18.0%), and 0/9 GPA (0%)). Motor neuropathy was observed in 19 patients (EGPA 14/19 (73.7%), MPA 5/61 (8.2%), GPA 0/9 (0%)). 15 patients had both sensory and motor neuropathies (EGPA 12/19 (63.2%), MPA 3/61 (4.9%), GPA 0 (0%)). In patients with both sensory and motor neuropathy, sensory impairment preceded in all cases. Among patients with neuropathy, the time from initial symptoms to initial induction therapy in patients with and without motor neuropathy was 34 ± 10.1 days and 30 ± 10.8 days (p = 0.776), respectively. Also, when comparing those who were treated within 7 days from the onset of movement disorders with those who were treated later, MMT score two weeks after the start of treatment were 92.15 ± 1.47 vs. 91.25 ± 2.65 (p = 0.77). Between the patients with EGPA with and without sensory neuropathy, there were no significant differences in the following: highest WBC(19620.0 ± 2082.6 vs. 19350.0 ± 4033.5 cells/uL (p = 0.953)), highest Eo(10790.6 ± 1774.8 vs 12440.8 ± 3436.9 cells/uL (p = 0.6750)), and highest CRP levels (4.467 ± 0.96 vs 2.70 ± 1.85 mg/dL (p = 0.41)) before the initial therapy. On the other hand, comparing the EGPA patients with and without motor neuron disorder, CRP levels were significantly higher in those with motor impairment than those without(WBC 20978.6 ± 2049.8 vs. 15600.0 ± 3429.9 cells/uL (p = 0.20); Eo 12213.4 ± 1775.5 vs. 8127.0 ± 2971.0 cells/uL (p = 0.25); CRP 5.13 ± 0.89 vs. 1.20 ± 1.48 mg/dL (p = 0.04)). And in patients with motor neuropathy, the decrease in MMT score was significantly correlated with the worst levels of CRP(p = 0.001)while the decrease was not correlated with the other blood tests. ANCA levels were not associated with sensory or motor neuropathy. In similar analyses of patients with MPA and GPA, there were no significant findings. Conclusion: Worst CRP levels before the initial therapy can be a poor prognosis factor for motor neuropathy in patients with EGPA. Therefore, EGPA patients with high CRP levels need to be paid more attention to because of possible development of motor neuropathy. Disclosure of Interests: satoshi hama: None declared, Yutaro Hayashi: None declared, Keisuke Izumi Grant/research support from: Asahi Kasei Pharma, Takeda Pharmaceutical Co., Ltd., Speakers bureau: Asahi Kasei Pharma Corp, Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Eli Lilly Japan K.K., Mitsubishi Tanabe Pharma Co., Misako Higashida-Konishi: None declared, mari ushikubo: None declared, kumiko akiya: None declared, yutaka okano: None declared, Hisaji Oshima: None declared